2011
DOI: 10.2478/v10033-011-0005-z
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Human Development Index Considering Unemployment

Abstract: An Alternative Human Development Index Considering UnemploymentThe Human Development Index (HDI) has played an influential role in the debate on human development (HD) for many years. However, no index is perfect and neither is the HDI of the United Nations Development Program (UNDP). This paper aims to construct a new composite index for the development performance of a sample of 30 Organization for Economic Co-operation and Development (OECD) countries by adding a fourth indicator, namely the unemployment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Various suggestions have been presented to this day to improve the accuracy while measuring human development, such as the inclusion of the workforce employment level and the unemployment level as the index's sub-dimensions and indicators (Taner et al, 2011). However, while education indicators are still included in HDI, unemployment, and employment criteria are not yet included in the index.…”
Section: Relationship Between Hdi Unemployment Neet and Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Various suggestions have been presented to this day to improve the accuracy while measuring human development, such as the inclusion of the workforce employment level and the unemployment level as the index's sub-dimensions and indicators (Taner et al, 2011). However, while education indicators are still included in HDI, unemployment, and employment criteria are not yet included in the index.…”
Section: Relationship Between Hdi Unemployment Neet and Educationmentioning
confidence: 99%
“…The analysis showed that the unemployment rates of people with lower or no education in developed countries have a positive effect on the GDP. Taner et al (2011) proposed an alternative HDI as the current HDI indicators do not include the employment and unemployment dimensions of human development. A comparison of the proposed index and the current index was conducted with the data of from OECD countries between the years 1998-2010 and the correlation analysis method.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Seu cálculo é semelhante ao do IDH, padronizando os indicadores usuais ao Índice de Sustentabilidade Ambiental (ISA). Taner et al (2011) sugerem um índice em que a quarta dimensão esteja atrelada ao nível de desemprego dos países. Segundo o estudo desses autores, embora não tenha sido incluída atualmente nos subíndices do IDH, a taxa de desemprego é um indicador de inclusão social e de qualidade de vida por vias da utilização eficiente dos recursos humanos.…”
Section: Novos Indicadoresunclassified
“…The instability of modern economic structures and the unevenness of external and internal economic shocks are accompanied by significant asymmetric cyclical fluctuations in the economic activity and employment in Ukraine, which has led lead to significant disturbances in the economic and social environment of the country [1][2]. In this regard, the implementing effectiveness of the market transformation regulatory measures in the Ukrainian economy, aimed at ensuring its socio-economic development, competitiveness and improvement of human capital [3] requires an in-depth theoretical and empirical investigation of the functioning peculiarities of the labour market, as well as modelling the dynamics of its main indicators [4].…”
Section: Introductionmentioning
confidence: 99%